Problematic Drug Use Among Outpatients With Schizophrenia and Related Psychoses - Chang, Sherilyn; Jeyagurunathan, Anitha; Lau, Jue Hua; Shafie, Saleha; Samari, Ellaisha; Cetty, Laxman; Mok, Yee Ming; Verma, Swapna; Subramaniam, Mythily (Frontiers in Psychiatry, 2021)
Background: Problematic drug use is common among psychiatric patients and is linked with poorer course and outcomes of illness. The aim of this study is to assess the prevalence of problematic drug use, and to explore its sociodemographic correlates and associations with health behaviors and outcomes among outpatients with schizophrenia and related psychoses in Singapore. Methods: Data from 397 individuals who were aged 21-65 years and were seeking treatment for schizophrenia and related psychoses in the outpatient clinics of a tertiary psychiatric hospital was analyzed. The Drug Abuse Screening Test (DAST-10) was used to assess problematic drug use. Information on sociodemographics, smoking status, alcohol use, symptoms severity and quality of life were collected. Multivariable logistic regressions were conducted to explore correlates and associations of problematic drug use. Results: The prevalence of problematic drug use was 5.8% (n=23) in the sample, and 10.6% (n=42) of the participants reported having problematic drug use and/or problematic alcohol use. More males than females reported having problematic drug use (p=0.021), and also problematic drug and/or alcohol use (p=0.004). Significant associations were observed between problematic drug use and smokers with nicotine dependence, and with physical health domain of quality of life. Individuals with greater symptom severity were approximately twice as likely to have problematic drug use and/or alcohol use. Conclusion: While the prevalence of problematic drug use in this sample population is relatively lower compared to other countries, there is a considerable number who might be at risk. Routine screening and close monitoring of drug use is recommended as part of psychiatric assessment, particularly among males and patients with nicotine dependence.